1985
DOI: 10.2307/1956249
|View full text |Cite
|
Sign up to set email alerts
|

The Bear Market in Political Socialization and the Costs of Misunderstood Psychological Theories

Abstract: Not so long ago, political scientists were enthusiastically proclaiming that political socialization was a growth stock. But interest in the subfield has slackened, and the bull market has turned bearish. This article argues that a central cause of this recent scholarly neglect is a lack of theoretical confidence. Political socialization has been branded as less worthy of study largely because it is difficult to study and to understand in the absence of an explicit psychological model of learning. A strong the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
52
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 39 publications
(30 reference statements)
0
52
1
Order By: Relevance
“…For example, Merelman [1971], Moore et al [1985], and numerous others have made use of Piaget's cognitive developmental theory to interpret selected results. Recently, Cook [1985] suggested that Vygotsky's theory might be used to understand young people's view of politics. Others have discussed atti tudes and knowledge as important compo nents of the outcomes of political socializa tion without much attention to broader the oretical constructs.…”
mentioning
confidence: 99%
“…For example, Merelman [1971], Moore et al [1985], and numerous others have made use of Piaget's cognitive developmental theory to interpret selected results. Recently, Cook [1985] suggested that Vygotsky's theory might be used to understand young people's view of politics. Others have discussed atti tudes and knowledge as important compo nents of the outcomes of political socializa tion without much attention to broader the oretical constructs.…”
mentioning
confidence: 99%
“…It has not been resusci tated largely because the reasons political scientists had paid attention to children's political learning were set by the 'political theory of political socialization', namely a concern with what is functional for the polit ical system to persist. There are other rea sons to study political socialization -notably to examine the question of whether individ uals develop their own political perspectives or whether they adopt others prepared for them [Connell and Goot, 1972;Sears, 1975;Lindblom, 1982;Cook, 1985]. Yet few em pirical studies have addressed this ques tion.…”
Section: Political Socialization As a Normal Sciencementioning
confidence: 99%
“…No single model has been advanced by analysts of political behavior as accounting for all political learning, and as Cook [1985] pointed out, researchers in political sociali zation have paid a price for 'misunderstood psychological theories'. At the beginning of this project, I considered cognitive develop mental models [Piaget, 1977] and social learning models [Bandura, 1986] to be at polar ends of a continuum, with the former attributing learning to internal, maturational factors and the latter attributing it to exter nal.…”
mentioning
confidence: 99%